25P Analysis of NGS-based blood immune cell RNA signatures for colorectal cancer detection. (15th December 2019) - Morgenthaler, S; Lindsay, H; Ciarloni, L; Angelino, P; Dorta, G; Delorenzi, M; Ehrensberger, S Hosseinian
Abstract: Background: Colorectal Cancer (CRC) is the second leading cause of cancer mortality worldwide. Effective and non-invasive biomarkers are needed to improve early diagnosis and disease management. Immune cells play a key role in tumor progression. Circulating immune cell count is a potential cancer biomarker, as indicated by the association of high blood neutrophil-to-lymphocyte ratio with poor prognosis in patients with cancer. The study goal was to determine the correlation between circulating immune cell counts and immune cell-specific RNA signatures and to evaluate the signature potential for CRC detection. Methods: The transcriptome profiles of peripheral blood mononuclear cells from 561 Asian and Caucasian subjects (189 CRC, 115 advanced adenomas, 39 other cancers, 218 controls without colorectal lesions (CON)) were generated by RNA-seq on the Illumina platform. Neutrophils, lymphocytes and monocytes counts were obtained by standard hematology testing. Specific RNA signatures for neutrophils, monocyte/macrophages, T cells, CD4, CD8, B cells, NK cells were compiled from literature. The mean expression level of all genes in each Immune cell signature was calculated and used for statistical analyses. Results: The main immune cell type RNA signatures showed correlation with the relative cell counts (r: 0.4-0.6), indicating the validity of the RNA signatures. Myeloid cell (monocyte/macrophage and neutrophil) RNA signatures were the most significantly upregulated in CRC compared to CON (p < 0.01), whereas the T-cell signature was the most significantly downregulated. Interestingly, the NK cell RNA signature was strongly upregulated in the Asian compared to Caucasian patients, which was mirrored by a higher lymphocyte cell count, in line with a previous study. Conclusion: This study shows that measuring specific immune cell type by RNA signatures correlate with traditional cell counting methods, enabling the extraction of valuable clinical information from blood transcriptomic data. This data suggests that both blood myeloid and T cells RNA signatures are promising biomarkers for CRC detection. Further biomarker development would require the optimization of the RNA signatures to validate and increase their diagnostic power. Legal entity responsible for the study: Novigenix. Funding: Novigenix. Disclosure: S. Morgenthaler: Advisory / Consultancy: Novigenix. L. Ciarloni: Shareholder / Stockholder / Stock options, Full / Part-time employment: Novigenix. G. Dorta: Advisory / Consultancy: Novigenix. S. Hosseinian Ehrensberger: Shareholder / Stockholder / Stock options, Full / Part-time employment: Novigenix. All other authors have declared no conflicts of interest.